PENINGKATAN KESADARAN GIZI SEIMBANG PADA REMAJA MELALUI EDUKASI DI MAN 1 BANDAR LAMPUNG - Sulya, Hana; Marta, Annisa Tiara; Jausal, Anisa Nuraisa; Maulana, Muhammad; Iyos, Rekha Nova; Wardhana, Muhammad Fitra (FK Unila, 2025)
Adolescents are a vulnerable age group prone to nutritional problems due to a lack of knowledge and awareness regarding healthy eating patterns and the importance of limiting sugar intake. This condition increases the risk of non-communicable diseases such as obesity, diabetes mellitus, and hypertension from a young age. This community service activity was carried out as part of the work program of the Community Service Department, BEM FK Unila, under the